Inovasi Guru PAI dalam Memanfaatkan Pembelajaran Berdiferensiasi Berbasis Teknologi Melalui Media Super Card for Super Gen Z - Siti Ahadiyah; Ayep Rosidi; Imam Anas Hadi (Universitas Muhammadiyah Magelang, 2026)
This Study aims to describe the innovation of Islamic Religious Education (PAI) teachers in utilizing technology-based differentiated learning through Super Card for Super Gen Z media and identify factors that support and hinder its implementation in learning. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation with analysis methods in the form of data reduction, data presentation, as well as drawing conclusions and verification. The subjects of this study were Islamic Religious Education (PAI) teachers and students in the classes studied. The result of the study indicate thar learning innovation through Super card media can help teachers accommodate differentiated learning in aspects of content, process, and learning products. This Super Card media helps teachers adjust the interests, readiness, and learning profiles of students so that learning can be more interactive, interesting, and student-centered. In addition, the use of Super Card media can also increase student motivation, activeness, and understanding of Islamic Religious Education (PAI) materials. Factors that support the implementation of this innovation include teacher creativity in developing media, the availability of technological facilities, school support and high student interest in technology. Obstacles that arise include limited internet access, differences in student technology skills, and limited time to prepare learning media. Therefore, this Super Card for Super Gen Z media could be an effective and relevant learning innovation to improve the quality of Islamic Religious Education (PAI) learning in the digital age.